Energy and Solar Irradiance Analysis for Hydroponic System - Nurul Nabilah binti Mat Ropi; Balila binti Mat Said; Nasarudin Ahmad; Hendri Novia Syamsir (SHM Publisher, 2023)
A Simulated impact of partial shadow on PV modules and the different partial shading on the PV panel effect on the PV performance is being analysed. The setting for the report is a hydroponic plant system equipped with a solar energy source and IoT at Pangsapuri Jasa, Mutiara Rini. The system control can reduce the carbon footprint and cause no pollution to the environment, while the information gathering process is faster without requiring a lot of time and energy. By collecting the data at Pangsapuri Jasa, the suitable irradiation data is used. The power consumption cannot be monitored by users. A shadow is casted over a panel which make the amount of sunlight reaching the surface is reduced. In addition, the partial shading effects continue to be one of the most demanding issues that directly influence the effectiveness of PV networks in terms of power outputs, the development of several peaks on the power-voltage (P-V) characteristic curve, and the incidence of hot-phenomena. Furthermore, the effective strategies are not being implemented that could save the energy consumption where analysis of the system performance is not practiced consistently when there are available strategies that can improve the system. The purpose of this project is to focus on analyzing the effect of the partial shading to the PV output performance. Also, to monitor the real time monitoring of electricity usage for hydroponic system. This project also covers the analysis of the effect of different configuration of shaded area of partial shadings on PV output performance. The study focuses on a specific kind of shading where photovoltaic panels as a shading device. The study focusses on the analysis of PV output performance on different partial shading conditions. Different number of shadings are being presented to display the experimental set up by using MATLAB Simulink